The language of flirtation of women and its effect on language formulation and style Lebanese poet Nahda al-Halabi as a model - , Hadeel Ali Kadhim (Thi Qar Arts Journal, 2021)
On the breadth of literature, whether poetry or prose, women were limited in comparison to that huge number of male poets, writers and orators. I do not mean by limited to a narrow framework. That is, if we enumerate the women of the pre-Islamic era with all that it contained of the famous women who shone in the sky of literature, and for whom a veil was drawn away from fame, we could embrace them in pages, as well as the Islamic era, even if it did not come to be counted. And I mean listing the classes of women in a specialized form by researchers. However, the previous eras, no matter how rich they were for us from women, the numbers remain limited. While our era, which has transformed the Internet, the whole world is a village, or even less than that, a small house, and with the culture becoming pervasive, and our countries and Arab countries have become free, women have become among men as if they are exceeding them in number, not only in literature but in all aspects of life. And if we examined social networking sites, and looked at poets, storytellers, writers of thoughts, linguists, and professors who delve into literature, history, criticism and writing, we would find it impossible to collocate the word “limited” with women.